Tinjauan Hukum Pidana terhadap Kekerasan dalam Rumah Tangga - R. Zainul Mushthofa; Siti Aminah (Universitas Sunan Drajat Lamongan, Indonesia, 2022)
The family is a social unit in society that has a very large role and influence in the family in social and personality development of each family member requires its own organization and needs the head of the household as an important figure who leads the family in addition to several other family members. A family is called harmonious if all members feel happy which is marked by the absence of conflict, tension, disappointment and satisfaction with the situation (physical, mental, emotional, and social). social) all family members. This legal research is a descriptive research and is included in the type of normative or doctrinal legal research. Location of research in the library and types of secondary data sources. Data collection techniques used are document studies, in the form of laws and regulations, books, journals, papers, articles and others. Analysis of the data used is content analysis (Content of analysis). Based on this research, it was found that domestic violence is a crime category (crime) in general. There are two formulations of problems that must be studied, namely: forms of domestic violence and legal protection for victims of violence. The form of domestic violence is any act against a person, especially a woman, which results in physical, psychological, and neglect of the household, including threats to commit acts, coercion or deprivation of liberty against the law and within the household.